Analisis Faktor-Faktor Yang Mempengaruhi Pemberian ASI Ekslusif Pada Bayi Di Puskesmas Talaga Jaya - Amanda Adityaningrum; Herlina Jusuf; Pradita Pristi Nusi (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2021)
Exclusive breastfeeding is breastfeeding for 6 months without providing complementary foods or drinks. The health center with the lowest achievement of exclusive breastfeeding, based on data from the Gorontalo Provincial Health Office, is the Talaga Jaya Health Center. The purpose of this study was to determine the factors that influence exclusive breastfeeding for infants at the Talaga Jaya Health Center. This research is a quantitative research. The population is all infants aged 7-11 months totaling 290 people and the sample amounting to 168 people. The sampling technique used is Accidental Sampling and the data analysis used is Logistic Regression. Mother's education, mother's occupation, implementation early initiation of breastfeeding and family support obtained a p-value (0.000) less than (0.05), while the support of health workers had a p-value (0.998) more than (0.05). The factors that influence exclusive breastfeeding for infants at the Talaga Jaya Health Center are mother's education, mother's occupation, implementation of early initiation of breastfeeding, and family support. It is recommended for family members to be able to participate in exclusive breastfeeding by providing support for mothers breastfeeding up to 6 months..ASI Ekslusif adalah pemberian ASI selama 6 bulan tanpa memberikan makanan atau minuman pendamping. Puskesmas dengan capaian ASI Ekslusif terendah, berdasarkan data dari Dinas Kesehatan Provinsi Gorontalo adalah Puskesmas Talaga Jaya. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi pemberian ASI Eksklusif pada bayi di Puskesmas Talaga Jaya. Penelitian ini merupakan penelitian Kuantitatif. Populasinya adalah seluruh bayi yang berumur 7-11 bulan berjumlah 290 orang dan sampel berjumlah 168 orang. Teknik sampling yang digunakan adalah Accindental Sampling dan analisis data yang digunakan adalah Regresi Logistik. Pendidikan ibu, pekerjaan ibu, pelaksanaan IMD dan dukungan keluarga memperoleh nilai p-value (0,000) kurang dari α (0,05), sedangkan dukungan petugas kesehatan memiliki nilai p-value (0,998) lebih dari α (0,05). Faktor-faktor yang mempengaruhi pemberian ASI Ekslusif pada bayi di Puskesmas Talaga Jaya adalah pendidikan ibu, pekerjaan ibu, pelaksanaan IMD, dan dukungan keluarga. Disarankan kepada anggota keluarga untuk dapat ikut berpartisipasi dalam pemberian ASI Eksklusif dengan cara memberikan dukungan selama ibu menyusui sampai 6 bulan.